Innovative educational tools development for food security: Engaging community voices in Tanzania. (February 2018) - Bonatti, Michelle; Schlindwein, Izabela; Lana, Marcos; Bundala, Nyamizi; Sieber, Stefan; Rybak, Constance
Highlights: Pedagogical methods serve to raise community voices and the critical thought about its problems reframing the images of future. Education for future humanity challenges involves rethinking our communicative channel and creating operational learning process. Educational tools based on Paulo Freire can be created to approach exceptionally challenging context. Abstract: Food security projects have to use tools to interact with communities in order to approach a chain of interconnected problems, as well as to engage the plurality of community voices/actors in a growing future challenges scenarios. This work presents innovative educational tool developed to engaging community voices to understand food insecurity and to create local solutions. The 16 workshops inspired on the theory of the Pedagogy of the Oppressed, involved a total of 270 participants across the four case studies in remote Tanzanian villages. The results show that community voices and local problem perceptions significantly differed between the case study regions, which had a strong impact on coping strategies and nutritional status. In Morogoro, e.g., food insecurity was mainly related to conflicts. Smallholders with anemia prefer to avoid meat and milk as these products come from livestock keepers who have destroyed their crop farm production. More than 70 local diverse solutions were identified. The acceptance of the educational tools used was highly appreciated at local level compared to more conventional procedures (e.g. questionnaires). The pedagogical methods applied in this work served to raise the communities' voices, to promote consciences about communities' problems, and reframing their images of the future. The understanding of community perceptions might help with the implementation of sustainable nutrition-sensitive innovations.